Spontaneous hepatic hematoma, case series. Hospital San Bartolomé, June 2014-May 2018 - Zapata Díaz, Betsy Micol (2019)
Objectives: To determine the incidence, epidemiological and clinical characteristics and medical-surgical management of patients with spontaneous hepatic hematoma (SHH) associated to the HELLP syndrome. Design: Descriptive, retrospective series of cases. Institution: Hospital Nacional Docente Madre Niño San Bartolomé, Lima, Peru. Participants: Women diagnosed with SHH. Interventions: Review of medical records of patients with SHH attended in the period May 2014 - May 2018. Results: We found eight cases of SHH, with an incidence of 1/3 632 births. The average maternal age was 32 years; all of them were multiparous, 62.5% with full-term pregnancies. The most frequent symptom was epigastric pain. Initial diagnosis of severe preeclampsia was determined in 62.5% of the cases, and all of them progressed to HELLP syndrome. Intracesarean SHH occurred in 37.5% of the cases and 62.5% presented in the puerperium. Initial surgical management was hepatic packing in 62.5%. All patients were hospitalized in the women’s intensive care unit (ICU) and 75% required blood transfusion or other blood products. The most frequent complications were anemia and liver abscess (75%). The average hospital stay was 27 days. There was one maternal death (12.5%). Conclusions: Hepatic hematoma is an obstetric emergency at our hospital with high risk of mortality and extreme morbidity. Clinical suspicion and early diagnosis were tools for timely decision making; surgical management was predominant.